Oxidative stress and quantum yield efficiency in the intertidal seagrass zostera noltii - Silva, João (2009)
We investigated the combined effects of several environmental stressors in the photosynthetic performance and in the activation of biochemical defense mechanisms in the intertidal seagrass Zostera noltii in Ria Formosa coastal lagoon (southern Portugal). The maximum (Fv/Fm) and the effective (F’v/F’m) quantum use efficiencies of PSII were sampled monthly in both neap and spring tides over one year. Other fluorescence parameters, such as the Stern-Volmer non-photochemical quenching (NPQ) and the novel parameter LNP (which expresses the general decrease in PSII photochemical activity in the light) were derived from quantum use efficiency measurements. Sampling for antioxidant enzymes activity, pigments, soluble protein and malondialdehyde (MDA) was conducted in parallel. Reactive oxygen species (ROS) are formed as a normal part of the metabolism. An increment on ROS formation is a common response to those stresses and can cause several types of damage, namely lipid peroxidation. MDA is a product of the peroxidation of membrane lipids and thus is commonly used as an indicator of oxidative stress. Carotenoids and antioxidant enzymes such as ascorbate peroxidase (APx) are part of the plants’ antioxidative system. Higher content of carotenoids indicate a higher photoprotection and increased activities of ROS scavenging enzymes such as APx are correlated with stress tolerance. The relationships among critical environmental parameters (irradiance, temperature, air exposure), oxidative stress, antioxidative responses and quantum use efficiency in Z. noltii were explored through multifactorial analysis.